Political Resistance Against Brown V. The Board of Education of Topeka 1954-1960 - Rojo, Anthony (The Toro Historical Review, 2023)
After the ruling of Brown V. The Board of Education that declared segregated public schools unconstitutional, the American South began to employ political means in order to maintain segregation. This fight to preserve segregation was seen throughout all levels of the American government, from the highest office of the presidency to local political organizations such as the White Citizens' Councils.